Data on Connexin 43 hemichannels regulation of cellular redox in lens - Yumeng Quan (Elsevier, 2021)
This article describes a dataset that is related to the research paper “Connexin hemichannels regulate redox potential via metabolite exchange and protect lens against cellular oxidative damage”. Growing evidence demonstrates that oxidative stress is a key event in cataract formation. Hemichannels (HCs) formed by Connexin (Cx) 43, a Cx subtype only present in the epithelium of lens tissue, mediate the exchange of small molecules between the intracellular and extracellular environments, including redox-related metabolic molecules, such as glutathione (GSH) and reactive oxygen species (ROS). Here, we used a Cx43 heterozygous mouse model, Cx43E2 antibody (a specific Cx43 HC blocker), and knocked down Cx43 expression by siRNA in human lens epithelial HLE-B3 cells to assess the oxidative response of Cx43 HCs to H2O2 and UVB radiation. Western blot analysis of heterozygous Cx43-null (Cx43+/−) mouse lenses showed the haploinsufficiency of Cx43 protein. We further assessed anti-oxidative gene expression in response to H2O2 and UVB radiation treatment in the Cx43-deficient lens epithelial cells. This dataset will be useful for understanding the critical role of Cx43 HCs in maintaining redox homeostasis in the lens under oxidative stress.